Nebengin: Aplikasi Transportasi Kolaboratif Berbasis Android - I Made Sukarsa; I Kadek Teo Prayoga Kartika; I Putu Arya Dharmadi (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Online transportation services are transportation services that take advantage of advances in information technology. In Indonesia, several online transportation service providers have grown, such as Gojek, Grab and several other startup startups. In addition to the many benefits and conveniences that have been provided, the service price factor is still felt expensive for the community, especially the lower classes. One solution is to build a Collaborative Transportation Application that utilizes the Collaborative Transportation Management (CTM) interaction method. The main features contained in the application, namely the feature of finding driver routes in the direction of the consumer route, online chat, and route management by utilizing the Android mobile application based on Google Map API and Firebase Cloud Messaging. Performance testing using JMeter from a total of 300 virtual users performs 6 HTTP requests resulting in an average response time of 0.852 alias tolerated according to Apdex standards. Based on the results of testing of 15 respondents obtained the results that this application is easy to use, supports traveling activities, fast response time when used, features provided are quite complete, an accurate position tracking system, unidirectional route search is very compatible with consumer routes, and the process of coordination and driver collaboration is very good so that the travel costs borne by consumers become more economical..